Dabigatran etexilate and reduction in serum apolipoprotein B. Issue 1 (9th November 2015) - Joseph, Philip; Pare, Guillaume; Wallentin, Lars; Connolly, Stuart; Yusuf, Salim; Wang, Jia; Ezekowitz, Michael; Eikelboom, John; Siegbahn, Agneta; Reilly, Paul; Themeles, Ellison; Oldgren, Jonas
Abstract : Objective: Carboxylesterases, which convert dabigatran etexilate to its active form, dabigatran, have also been shown to influence lipoprotein metabolism, although any pleotropic effects of the drug based on this possible mechanism has not been evaluated. We examined the effects of dabigatran etexilate on serum lipoprotein markers in the Randomized Evaluation of Long-Term Anticoagulation Therapy (RE-LY) study. Methods: 2513 participants from the RE-LY randomised control trial with baseline and 3-month apolipoprotein B (ApoB) and apolipoprotein A1 (ApoA1) measurements were included. We prospectively compared the effects of dabigatran 110 mg twice daily, dabigatran 150 mg twice daily and warfarin on changes in ApoB and ApoA1 concentrations using a mixed model analysis. Results: From baseline to 3 months, a significant reduction in ApoB concentration was observed with low-dose dabigatran (−0.057 (95% CI −0.069 to −0.044) g/L, p<0.001) and high-dose dabigatran (−0.065 (95% CI −0.078 to −0.053) g/L, p<0.001) but not warfarin (−0.006 g/L (95% CI −0.018 to 0.007) g/L, p=0.40). Compared with warfarin, ApoB reduction was significantly greater with both doses of dabigatran (p<0.001 for both groups). Reductions in ApoA1 concentrations did not statistically differ with either dose of dabigatran when compared with warfarin. Conclusions: Dabigatran is associated with a significant (∼7%) reduction in ApoB concentration, suggesting a novel effect of this drug on lipoprotein metabolism. Further studies are needed to determine the mechanism of this observed effect, and its impact on clinical outcomes.